Pengaruh ROE, GWM, dan Beban Promosi terhadap Penerimaan Dana ZISWAF pada Perbankan Syariah dengan Firm Size sebagai Variabel Moderasi Periode Tahun 2015.Q1 – Tahun 2023.Q3 - Agustina Anggrainie; Eka Wahyu Hestya Budianto (Jurnal Ilmiah Ekonomi Syariah, 2024)
This research aims to determine the influence of ROE, GWM and promotional expenses on the receipt of ZISWAF funds in Islamic banking with firm size, and the receipt of ziswaf funds on the influence of ROE, GWM and promotional expenses. The samples used in this research were companies in the financial sector or Sharia banks in Indonesia in 2018-2023. The sampling technique used was observation, with a total sample of 5 banks over 6 years. The data analysis technique used is the T test and coefficient of determination test with the Eviews 12 application. The results of the research show whether there is a significant negative or positive effect on the value of financial sector companies for the 2018-2023 period. Capital structure has a significant negative effect on the value of financial sector companies for the 2018-2023 period. Profitability is able to moderate the influence of institutional ownership on the value of financial sector companies for the 2018-2023 period. Profitability is able to moderate the influence of ROE, GWM and Promotional Expenses on the value of financial sector companies for the 2018-2023 period. In future research, it is hoped that other variables will be used as moderating variables, such as dividend policy and sample companies from other sectors so that the research results can also represent other financial business sectors.This research aims to determine the influence of ROE, GWM and promotional expenses on the receipt of ZISWAF funds in Islamic banking with firm size, and the receipt of ziswaf funds on the influence of ROE, GWM and promotional expenses. The samples used in this research were companies in the financial sector or Sharia banks in Indonesia in 2018-2023. The sampling technique used was observation, with a total sample of 5 banks over 6 years. The data analysis technique used is the T test and coefficient of determination test with the Eviews 12 application. The results of the research show whether there is a significant negative or positive effect on the value of financial sector companies for the 2018-2023 period. Capital structure has a significant negative effect on the value of financial sector companies for the 2018-2023 period. Profitability is able to moderate the influence of institutional ownership on the value of financial sector companies for the 2018-2023 period. Profitability is able to moderate the influence of ROE, GWM and Promotional Expenses on the value of financial sector companies for the 2018-2023 period. In future research, it is hoped that other variables will be used as moderating variables, such as dividend policy and sample companies from other sectors so that the research results can also represent other financial business sectors.This research aims to determine the influence of ROE, GWM and promotional expenses on the receipt of ZISWAF funds in Islamic banking with firm size, and the receipt of ziswaf funds on the influence of ROE, GWM and promotional expenses. The samples used in this research were companies in the financial sector or Sharia banks in Indonesia in 2018-2023. The sampling technique used was observation, with a total sample of 5 banks over 6 years. The data analysis technique used is the T test and coefficient of determination test with the Eviews 12 application. The results of the research show whether there is a significant negative or positive effect on the value of financial sector companies for the 2018-2023 period. Capital structure has a significant negative effect on the value of financial sector companies for the 2018-2023 period. Profitability is able to moderate the influence of institutional ownership on the value of financial sector companies for the 2018-2023 period. Profitability is able to moderate the influence of ROE, GWM and Promotional Expenses on the value of financial sector companies for the 2018-2023 period. In future research, it is hoped that other variables will be used as moderating variables, such as dividend policy and sample companies from other sectors so that the research results can also represent other financial business sectors.